2014
DOI: 10.30976/susead.302221
|View full text |Cite
|
Sign up to set email alerts
|

Nepoti̇zm Ve Örğütsel Bağlilik Arasindaki̇ İli̇şki̇ni̇n İncelenmesi̇ Ve Bi̇r Uygulama

Abstract: ÖZET Bu çalıĢmada çalıĢanların nepotizm algısının, üyesi oldukları örgüte olan bağlılıkları üzerine etkisi incelenmiĢtir. ĠĢ görenlerdeki nepotizm algısı; terfide kayırmacılık, iĢe alma sürecinde kayırmacılık ve iĢlem kayırmacılığı olmak üzere üç boyutta ele alınmıĢtır. Ayrıca ÇalıĢanların iĢletmeye olan bağlılıkları da duygusal bağlılık, devam bağlılığı ve normatif bağlılık olmak üzere üç farklı boyutta incelenmiĢtir. Bu çalıĢmada anket tekniği kullanılarak, nepotizm ve örgütsel bağlılık arasında anlamlı bir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 2 publications
0
3
0
3
Order By: Relevance
“…Some similar studies have been conducted directly and indirectly in Turkey and abroad on the favouritism behaviours of school administrators. For example; some studies have been made by Aydogan (2008Aydogan ( , 2009Aydogan ( , 2012, Meric (2012), Polat and Kazak (2014), Karahan and Yılmaz (2014), Aydın (2015), Argon (2015), Gecer (2015), Salcı (2015), Karademir (2016), Okcu and Ucar (2016) in Turkey; and in other countries, some research have been made by Pounder and Blase (1988), Abdalla, Magharabi and Ragged (1998), Laker and Williams (2003), Garicano, Palacios-Huerto and Prendergast (2005), Demaj (2012), Chandler (2012) and Moharib (2013). The most similar researches and related findings from these researches are summarized below: Aydogan (2009) tried to determine if there was favouritism in the Turkish education system.…”
Section: Service Favourtisimmentioning
confidence: 99%
See 1 more Smart Citation
“…Some similar studies have been conducted directly and indirectly in Turkey and abroad on the favouritism behaviours of school administrators. For example; some studies have been made by Aydogan (2008Aydogan ( , 2009Aydogan ( , 2012, Meric (2012), Polat and Kazak (2014), Karahan and Yılmaz (2014), Aydın (2015), Argon (2015), Gecer (2015), Salcı (2015), Karademir (2016), Okcu and Ucar (2016) in Turkey; and in other countries, some research have been made by Pounder and Blase (1988), Abdalla, Magharabi and Ragged (1998), Laker and Williams (2003), Garicano, Palacios-Huerto and Prendergast (2005), Demaj (2012), Chandler (2012) and Moharib (2013). The most similar researches and related findings from these researches are summarized below: Aydogan (2009) tried to determine if there was favouritism in the Turkish education system.…”
Section: Service Favourtisimmentioning
confidence: 99%
“…In this study, it was determined that there was a meaningful and negative relationship between the favouritism behaviours and attitudes of school administrators and teachers' perceptions regarding organizational justice. In a study conducted by Karahan and Yılmaz (2014) it was concluded that there was a decrease in the commitment levels of the employees to the organization as the frequency of exposure to the nepotism increased.…”
Section: Service Favourtisimmentioning
confidence: 99%
“…These findings reveal that leaders' sensitivities toward employees' needs is related to having a clearer vision ofthe organization as well as to stating more clearly the objectives and values of the organization as they relate to organizational commitment. This research underlines the strategic role of managers, one which has been changing for a while now (Rowden, 1999;Karahan, 2008). Cetin, Korkmaz and Cakmakci's study (2012) of transformational and transectional leadership effects and the interaction between leaders and members on teachers' organizational citizenship behaviors revealed that teachers exhibit organizational citizenship behaviors at a moderate level.…”
Section: The Relationship Between Change Leadership and Organizationa...mentioning
confidence: 66%
“…Bu doğrultuda yıldırma zorbaları saldırganlık eğiliminin daha çok etkisi altındadır ve düşmanlık duygusu yüksektir. Bu nedenle, kendilerine seçtikleri düşmanı zayıflatmak ve ortadan kaldırmak için ellerinden gelen her şeyi yaparlar (Karahan & Yılmaz, 2014). Bir başka yıldırma taraftarı gözlemcilerdir.…”
Section: 2unclassified